Investigating The Role of Celebrity Endorser Credibility On Product Purchase Intention - Soni Harsono; Fahmi Rachmat Setyawan; Nur Raafi Setiawan; Fikri Haikal (Journal of Economics, Business, and Accountancy Ventura, 2026)
This study aims to examine the relationship between various factors related to celebrity endorsers, in this case physical appearance, celebrity congruence, attractiveness, expertise, celebrity identification and trustworthiness on the purchase intention of shoes and electronic products. Data were obtained through a survey of 355 consumers who were exposed to advertisements using celebrities as endorsers. Data analysis using Partial Least Squares-based structural equation modeling (PLS-SEM). The results of the analysis show that physical appearance and celebrity congruence have a significant positive effect on purchase intention. In addition, celebrity attractiveness and expertise also have a significant effect on celebrity identification. However, trustworthiness does not play a role in moderating the relationship between physical appearance, attractiveness and purchase intention. Furthermore, trustworthiness also does not play a role in moderating the relationship between celebrity congruence, expertise and celebrity identification. Finally, celebrity identification has a significant positive effect on product purchase intention. These findings indicate that celebrity endorser-related factors have a significant impact on consumer purchase intention, except for the role of trustworthiness in moderating the relationship between these variables.